Building Resilient Leaders in a Time of Crisis: The Case of Credit Agricole Ukraine and KROK Business School - (:unkn) unknown (EFMD Global, 2025)
In the Eye of the Storm: Why Resilient Leadership Matters More Than Ever In times of war, when it seems that the system is falling, it is people who become the main capital of both companies and the country. Amid the war in Ukraine, Credit Agricole and KROK Business School launched in Kyiv a bold leadership programme to foster resilience, emotional intelligence, and innovation. The initiative, developed under constant uncertainty, resulted in tangible business impact and a cultural shift in leadership. Here’s how it happened – and why it earned international recognition.
Keywords: Credit Agricole Ukraine; KROK Business School; Бізнес Школа КРОК